Etyka galenosfery - Lepa, bp Adam (Annales. Etyka w Życiu Gospodarczym, 2011)
Galenosphere is an environment of silence. The paper addresses the issue of the essence and significance of galenosphere. To this end,it presents the structure and functioning of galenosphere, i.e. its two crucial components. Moreover, the structure of galenosphere includesstatic and dynamic elements. The latter determine the functioning of this type of environment. Eight most important sectors that affectthe operation of galenosphere were identified. Some of them (the culture of language, noise elimination, creating an environment promotingsilence and a prayer for silence) contribute to the emergence of a structured environment of silence, whereas others (positive attitude towardscalming down, concentration of the mind and emotions, inner concentration and the ability to be silent) constitute components which directlyparticipate in the formation of an environment of silence. A structured environment of silence is the most effective in operation.The paper points out various advantages offered to the human being by a structured galenosphere. The most significant ones include:successful self-improvement, improvement of spoken and written language skills, effective pedagogic activities, establishing goodrelationships with other people and getting a deeper insight into the sense of life. The discussion leads to the conclusion that the human beingshould be provided with optimal working conditions and conditions for development in various areas by the formation of a structuredgalenosphere (in the family, at school, in the office, etc.).